Trindade e Fátima: aspectos econômicos do turismo religioso - Silva, Dalva Pedro da (2016)
The religious tourism stimulates the economy of several cities in Brazil and Portugal, with the majority of them located in the interior of the two countries. In view of this representation, the objective of analyzing the relationship between the economic aspects, such as the profit produced in sanctuaries, and the actual aspect of religious pilgrimages to the shrines of Fatima Portugal and Trinity Goiás Brazil. The research took a qualitative methodology and resorted to bibliographical research, in addition to numerous on-site visits. The thesis is structured in three chapters: the first dedicated to the concept and to the historical context of social tourism. The second sought to treat in depth of religious tourism in Trinidad and in Fatima. The third focused on specifically the study of the economic aspects of the pilgrimage to two shrines, such as the economic impact that religious tourism brings to both cities and their surroundings.